Logiques paysannes, production agricole et lutte contre les ravageurs des cultures à Salcedo dans les Andes équatoriennes : stratégies individuelles ou collectives ? - Nasser Rebaï; François Rebaudo; Julien Rebotier; Olivier Dangles (VertigO)
In Ecuador, the debate on the future of family farming is still very important because of the high vulnerability of peasant communities, particularly in the Andean region, and of the worrying food situation in rural areas. In this context, the fight against crop pests, identified by the FAO as a priority to reduce food insecurity of farmers in the South, appears to be a major challenge for farming communities of the Ecuadorian sierra. However, the success of this struggle still remains limited because of the weak coordination of the farmers. Based on fieldwork conducted in the province of Cotopaxi, this paper points out the determinants of the lack of collective action against crop pests as it opens a discussion on the need of a greater collaboration between environmental and social sciences in order to consider the most effective strategies to strengthen the farmers coordination in the fight against crop pests and to increase their food security.